(3CSQGQ GdYQHjIs - (3YHO GdQMef Hf eMeO Hf YHjO Gddg GdCfUGQj , GHf GdCfHGQj, ceGd GdOjf CHh GdHQcGJ,J (B577 (3g` s ((3CMeO Hf CHj HcQ Hf CHj ESMGb GdEQHdi s)
(3ChdgG (B:s
(3GdMeO ddg cGTa GdXde eGfM GdYdG Pi GdLhO hHYO abO PcQJ ai gPG GdcJGH GdehShe HCSQGQ GdYQHjI cKjQkG ef ePGgH GdfMhjjf s
(3BNQgG (B:s
(3hgPG cdg djS HeWQO ai GdbjGS hEfeG OYGge Edi Pdc cKQI GdESJYeGd hgh ef GdTGP GdPi dGjbGS Ydjg Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3GfXQ GdLRA GdChd (B9 (3fMhs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs